Matharpacady-25.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The six-pointed Star of Bethlehem is associated with the Nativity story. The star served as a navigation aid for the three wise men who visited the manger where Jesus was born. It represents the divine light and hope brought into the world by the birth of Jesus Christ. This star of Bethlehem, stored in the open veranda at 20 Mataharpacady, will be hoisted during Christmas.